The role of minimally invasive surgery in epithelial ovarian cancer treatment: a narrative review - Generali, Matteo; Annunziata, Gianluca; Pirillo, Debora; D’Ippolito, Giovanni; Ciarlini, Gino; Aguzzoli, Lorenzo; Mandato, Vincenzo Dario (Frontiers in Medicine, 2023)
Objectives The aim of this narrative review is to summarize the available evidence on the use of minimal invasive surgery (MIS) in the management of epithelial ovarian cancer (EOC). Background MIS is currently performed to stage and treat EOC at different stage of presentation. We will evaluate risks and benefits of minimally invasive surgery for early stage EOC treatment, then potential advantages provided by staging laparoscopy in identifying patients suitable for primary cytoreductive surgery (PDS) will be discussed. Finally we will investigate the growing role of MIS in the treatment of advanced EOC after neoadjuvant chemotherapy (NACT) and in the treatment of EOC recurrence. Methods An electronic database search was performed on PubMed, Medline, and Google Scholar for relevant studies up to December 2022. Conclusion LPS represents a feasible surgical procedure for the staging and treatment in early, advanced and EOC relapse in selected patients treated in high-volume oncological centers by surgeons with adequate experience in advanced surgical procedures. Despite the increasing use of MIS over the last few years, randomized clinical trials are still needed to prove its effectiveness.